Introducción: Eco-ficciones, la metáfora animal y los estudios irlandeses - Estévez-Saá, Margarita; Manuela Palacios-González; Noemí Pereira-Ares (Estudios Irlandeses, 2020)
Nature, animals, the landscape and the environment have enjoyed a recurrent presence and have indeed been constant protagonists in Irish literature and culture. The wild isolated island, originally feared or even despised by foreigners, progressively became that romanticised, pre-modern Arcadia imagined by tourists from the early twentieth century onwards. The once desolated and barren landscapes of the Great Hunger were imaginatively recreated as green pastures, nostalgically conjured up by nineteenth- and twentieth-century Irish emigrants across the world. More recently, during the decades of the economic boom, the Irish land of the Celtic Tiger was plundered mercilessly by unscrupulous property developers, and its historical sites and natural resources were appropriated as commodities for tourism. These are just some examples of the many uses and abuses of the Irish environment in the recent cultural history of the island.